The anthropology of Buddhism and Hinduism : Weberian themes - Gellner, David N.; Weber, Max, 1864-1920. (New Delhi ; New York : Oxford University Press, 2001)
With reference to Nepal.
Includes bibliographical references (p. [348]-374) and index.
Keywords: Buddhism -- Social aspects -- Nepal; Hinduism -- Social aspects -- Nepal